ANALISIS KEPUASAN KERJA PEGAWAI PUSKESMAS BALIKPAPAN BARAT MELALUI DISIPLIN KERJA - Yuliani, Tutik; Arrywibowo, Imam; Abhirama Hanif, Muhammad (MEDIA RISET EKONOMI [MR.EKO], 2025)
Job satisfaction is a feeling that someone has in completing their work, this feeling can be a feeling of satisfaction or dissatisfaction. In an organization in achieving the goals that have been set, it is necessary to pay attention to employee satisfaction, because with the feeling of satisfaction that employees have will have a positive impact on their work, so that the goals desired by an organization or company will be achieved. This study aims to analyze the effect of motivation on satisfaction mediated by work discipline on employees of the West Balikpapan Community Health Center. In addition, this study also aims to determine the direct effect of motivation on the work discipline of employees of the Community Health Center in West Balikpapan and to determine the effect of work discipline on the job satisfaction of employees of the West Balikpapan Community Health Center. The variables used in this study are motivation, work discipline and job satisfaction. In this study, the population was limited to employees of the Kariangau Community Health Center in West Balikpapan District, totaling 318 employees. The sampling technique used in this study was a random sampling technique, namely a sampling technique by giving equal opportunities to the population to be sampled. Sampling using the Slovin formula was obtained at 43. The data used were primary data and secondary data. The primary data collection method used questionnaires and interviews, while the secondary data collection method used observation and documents. The analysis technique used the SmartPLS application. The results of the study indicate that motivation influences job satisfaction, mediated by work discipline among employees at the West Balikpapan Community Health Center. Motivation influences work discipline among employees at the West Balikpapan Community Health Center. Work discipline influences job satisfaction among employees at the West Balikpapan Community Health Center.